Collision severity analysis of quadrotors on covered linkways for ground risk assessment in urbanized environments - Mohd Hasrizam Che Man (2023)
With the promise to revolutionize many industries, the popularity of Unmanned Aerial Vehicles (UAVs) has surged in the last two decades. The use of multirotor UAVs in urban areas is gaining traction, with applications such as cargo delivery, emergency response, and recreational flight. However, unlike manned aviation, UAVs do not have a standardized design, testing, and certification procedures. Hence, a lot of countries raised their concerns about the risk of potential multi-rotor UAV crashes and impacting pedestrians on the ground. Apart from high-rise buildings, covered linkways are a ubiquitous sight in countries like Singapore with a primary role to provide shelter for pedestrians in the event of rain. Therefore, this study investigates the collision severity of a multirotor UAV impacting a covered linkway. Briefly put, the level of protection that covered linkways can provide to pedestrians from a multirotor UAV falling from height is analyzed. The methodology in this study is divided into three phases. In Phase 1, Finite Element Analysis (FEA) is employed to simulate the impact of two specific multirotor UAV designs and solid spheres with comparable material properties as they collide onto a simplified covered linkway panel using ABAQUS/CAE. Subsequently, parametric analysis using Python scripting is performed to assess the collision severity due to variations in mass and crash speed of rigid sphere. Phases 2 and 3 explore the impact of the honeycomb structure modelling on the impact simulation. Findings from this study will be beneficial for the computation of sheltering factor in UAV ground risk assessment.